Waqf for Economic Empowerment in Indonesia: Assessing the Effect of Institutional Trust and Waqf Innovation Using SEM-PLS - Rina Nur Shabrina; Aminah Nuriyah; Shofi Arofatul Marits (Faculty of Islamic Business and Management, 2025)
Waqf is an Islamic philanthropic instrument with significant potential to support sustainable economic empowerment in society. In Indonesia, the realization of productive waqf remains suboptimal, despite the estimated potential of cash waqf exceeding IDR 180 trillion annually. Low public participation in productive waqf is partly due to a lack of trust in waqf management institutions (institutional trust) and limited innovation in waqf practices (waqf innovation). This study aims to examine the influence of institutional trust and waqf innovation on waqf participation intention, and its impact on economic empowerment, with waqf participation intention as a mediating variable. A quantitative approach was employed using the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method. Data were collected through an online questionnaire involving 150 Muslim respondents in Indonesia who are familiar with waqf programs. The results reveal that both institutional trust and waqf innovation significantly affect waqf participation intention. Furthermore, waqf participation intention positively influences economic empowerment and mediates the relationship between institutional trust, waqf innovation, and economic empowerment. These findings highlight the crucial role of enhancing trust and innovation in optimizing waqf as a sustainable and inclusive tool for economic empowerment in Indonesia.